Microglia in morphine tolerance: cellular and molecular mechanisms and therapeutic potential - Zhang, Xiangning; Jin, Tingting; Wang, Haixia; Han, Shuai; Liang, Yongxin (Frontiers in Pharmacology, 2024)
Morphine has a crucial role in treating both moderate to severe pain and chronic pain. However, prolonged administration of morphine can lead to tolerance of analgesia, resulting in increased doses and poor treatment of pain. Many patients, such as those with terminal cancer, require high doses of morphine for long periods. Addressing morphine tolerance can help this group of patients to escape pain, and the mechanisms behind this need to be investigated. Microglia are the key cells involved in morphine tolerance and chronic morphine administration leads to microglia activation, which in turn leads to activation of internal microglia signalling pathways and protein transcription, ultimately leading to the release of inflammatory factors. Inhibiting the activation of microglia internal signalling pathways can reduce morphine tolerance. However, the exact mechanism of how morphine acts on microglia and ultimately leads to tolerance is unknown. This article discusses the mechanisms of morphine induced microglia activation, reviews the signalling pathways within microglia and the associated therapeutic targets and possible drugs, and provides possible directions for clinical prevention or retardation of morphine induced analgesic tolerance.